2005
DOI: 10.1002/jbm.a.30541
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alginate purification methods: Effect on polyphenol, endotoxin, and protein contamination

Abstract: Alginate, a polysaccharide extracted from brown seaweed, is widely used for the microencapsulation of islets of Langerhans, allowing their transplantation without immunosuppression. This natural polymer is known to be largely contaminated. The implantation of islets encapsulated using unpurified alginate leads to the development of fibrotic cell overgrowth around the microcapsules and normalization of the blood glucose is restricted to a very short period if it is achieved at all. Several research groups have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 38 publications
(48 reference statements)
2
106
0
5
Order By: Relevance
“…The three methods were specifi cally aimed at lowering concentrations of polyphenols, endotoxins and proteins in crude alginate, of which they were all successful, albeit to varying degrees. However, the most convincing results were obtained by Klock [ 10 ]. Upon further modifi cation to the technique devised by Klock et al incorporating size exclusion preparative chromatography and further dialysis, subsequent endeavors resulted in protein concentrations that were reduced by up to 90 %.…”
Section: Alginate Puritymentioning
confidence: 99%
See 2 more Smart Citations
“…The three methods were specifi cally aimed at lowering concentrations of polyphenols, endotoxins and proteins in crude alginate, of which they were all successful, albeit to varying degrees. However, the most convincing results were obtained by Klock [ 10 ]. Upon further modifi cation to the technique devised by Klock et al incorporating size exclusion preparative chromatography and further dialysis, subsequent endeavors resulted in protein concentrations that were reduced by up to 90 %.…”
Section: Alginate Puritymentioning
confidence: 99%
“…However, the subsequent development of multiple, albeit unstandardized, purifi cation techniques have warranted further comparative investigations. In an evaluation of the effectiveness of three in-house alginate purifi cation procedures designed by Prokop and Wang, de Vos et al, and Klock et al as opposed to using crude, unpurifi ed, and commercially available purifi ed alginate, all three groups reported varying results [ 10 ]. The three methods were specifi cally aimed at lowering concentrations of polyphenols, endotoxins and proteins in crude alginate, of which they were all successful, albeit to varying degrees.…”
Section: Alginate Puritymentioning
confidence: 99%
See 1 more Smart Citation
“…A shoulder was observed around 250-290 nm. Absorbance within the 250-290 nm range is commonly attributed to π − π* electron transitions in aromatic and poly-aromatic compounds [22], which could connect with the impurities such as humic acid, phenol, DNA or proteins [23]. The decrease of the …”
Section: Electronic Spectrummentioning
confidence: 99%
“…Among them, Alginate is quickly gelatinized with divalent cations, such as calcium chloride and barium chloride and has possibility for using on diverse parts due to including cells and drugs (25). However, because of contaminants, such as protein and endotoxin in the Alginate, some recent studies have shown the results that proliferation and adhesion of cells on alginate films were reduced (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%